Advanced kinetic modelling and simulation of a new small modular ammonia production unit. (8th June 2021) - Chehade, Ghassan; Dincer, Ibrahim
Highlights: A new kinetic modelling technique is developed for green ammonia synthesis. An operating pressure of 80 to 120 bar is feasible for the small ammonia converter. The Comsol model illustrates the diffusion phenomena inside the reactor. Abstract: This study aims to propose and develop a novel small modular ammonia synthesizer that enables ammonia to be produced on demand for the consumer with zero carbon emissions and less energy-intensive than conventional, large scale Haber-Bosch plants. A two-dimensional mathematical model is developed for simulation of a newly designed small modular ammonia converter with a total volume of 4.5 L. Thus, the developed integrated models consider all the physical and chemical processes in the reactor to accurately predict the reactor operating conditions. Both mass and energy balance equations are solved in the Matlab, while the transport equations to evaluate and account for the diffusional resistance to the transport of reactants and products in the catalyst pores are solved in the Comsol. Also, the temperature, component mole fraction, nitrogen conversion, and effectiveness factor of the newly designed ammonia converter are predicted and investigated by varying the total input flow, feed composition, pressure, and inlet temperature. The modeling results show that a pressure range of 80 bar to 120 bar is suitable and feasible for the proposed modular ammonia converter where the maximum attained temperature is found to 745 K and the feed flow rate is found to be 0.9399 m 3 /h. While the Comsol modeling results show that the formation of ammonia at the surface of the catalyst proceeds up to 4 mol% when the position of the concentration profile is between 20 and 60 vol% and the space velocity is 0.59 s. The simulation results compared to experimental and plant data are in very good agreement.